2007
DOI: 10.1038/sj.ijir.3901596
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sildenafil administration on penile hypoxia induced by cavernous neurotomy in the rat

Abstract: Hypoxia is a normal, physiological condition in penile tissue, which is interrupted by reoxygenation associated to sleep-related erections. We previously described in the rat that a penile fibrosis and overexpression of the pro-fibrotic endothelin-1 type B receptor (ETB) are associated to prolonged (3 months) hypoxia induced by the bilateral surgical resection of the cavernous nerves (bilateral cavernous neurotomy (BCN)). The aim of the present study was to define the time frame in which BCN induces hypoxia an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
39
0
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 41 publications
4
39
0
1
Order By: Relevance
“…They found that chronic tadalafil treatment almost completely restored penile oxygenation and the ratio of smooth muscle and fibrous tissue at histology. Similar results were obtained by the same group using sildenafil and vardenafil [45,46]. In a very recent report, Lysiak and colleagues demonstrated a protective role of chronic tadalafil administration on mice subjected to cavernous nerve resection or sham surgery [47].…”
Section: Rationale For Phosphodiesterase Type 5 Inhibitor Prophylaxissupporting
confidence: 73%
“…They found that chronic tadalafil treatment almost completely restored penile oxygenation and the ratio of smooth muscle and fibrous tissue at histology. Similar results were obtained by the same group using sildenafil and vardenafil [45,46]. In a very recent report, Lysiak and colleagues demonstrated a protective role of chronic tadalafil administration on mice subjected to cavernous nerve resection or sham surgery [47].…”
Section: Rationale For Phosphodiesterase Type 5 Inhibitor Prophylaxissupporting
confidence: 73%
“…However, in a recent clinical study Montorsi et al 40 proposed that on-demand vardenafil treatment is the best option for the treatment of ED in men after bilateral Sildenafil citrate and mononuclear cells J García-Cardoso et al nerve-sparing radical prostatectomy with respect to daily administration. Similar results were also recently obtained by Vignozzi et al 41 in a rat experimental model of penile hypoxia showing that PDE5 inhibitors treatment should be started as soon as possible. This study only compared the effect of one and two sildenafil citrate doses on the NO/cGMP system in mononuclear cells, so we cannot rule out the possibility that the use of sildenafil citrate on a daily basis may exerts additional effects on the levels of the proteins involved in the NO/cGMP system in mononuclear cells, which should be further studied.…”
Section: Sildenafil Citrate and Mononuclear Cells J García-cardoso Et Alsupporting
confidence: 76%
“…PDE-5s seem to prevent the endothelial damage related to ischaemia-reperfusion and denervation [14,15]. Furthermore, recent studies underline the use of sildenafil after RP to be associated with preservation of smooth-muscle content within the corpora cavernosa [15][16][17]. The natural recovery of EF seems to take place as long as 24 months and the early institution of medical therapy, specifically intracorporal injections, after 2 months post-operatively has resulted in a higher incidence of spontaneous return of erections at 1 year [2].…”
Section: Discussionmentioning
confidence: 98%